Characterization of a trinuclear ruthenium species in catalytic water oxidation by Ru(bda)(pic)2 in neutral media. Issue 55 (22nd June 2016) - Zhang, Biaobiao; Li, Fei; Zhang, Rong; Ma, Chengbing; Chen, Lin; Sun, Licheng
Abstract : A Ru III –O–Ru IV –O–Ru III type trinuclear intermediate was crystallographically characterized in catalytic water oxidation. Hindering the formation of the trinuclear intermediate by pH adjustment led to a great improvement in the catalytic activity. Abstract : A Ru III –O–Ru IV –O–Ru III type trinuclear species was crystallographically characterized in water oxidation by Ru(bda)(pic)2 (H2 bda = 2, 2′-bipyridine-6, 6′-dicarboxylic acid; pic = 4-picoline) under neutral conditions. The formation of a ruthenium trimer due to the reaction of Ru IV O with Ru II –OH2 was fully confirmed by chemical, electrochemical and photochemical methods. Since the oxidation of the trimer was proposed to lead to catalyst decomposition, the photocatalytic water oxidation activity was rationally improved by the suppression of the formation of the trimer.